2007
DOI: 10.1111/j.1939-1676.2007.tb03045.x
|View full text |Cite
|
Sign up to set email alerts
|

Argyrophilic Nucleolar Organizing Regions and Ki67 Equally Reflect Proliferation in Fine Needle Aspirates of Normal, Hyperplastic, Inflamed, and Neoplastic Canine Lymph Nodes (n = 101)

Abstract: Background: The count of argyrophilic nucleolar organizing regions (AgNOR) has been considered a useful variable that reflects cellular proliferation in canine lymph nodes, but it has not been compared with other markers of proliferation.Hypothesis: Ki67 and AgNORs are equally useful as markers of tissue proliferation in fine needle aspirates of canine lymph nodes.Animals: A total of 101 dogs. Material and Methods: Prospective, observational study of a convenience sample of dogs. Two smears were prepared for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 28 publications
2
15
1
Order By: Relevance
“…Ki67 ICC has also proved to be an excellent method of differentiation between non-neoplastic and neoplastic proliferation of lymphatic tissue (Bauer et al 2007, Fernandes et al 2015. Moreover, Fournel--Fleury et al (1997b) have confirmed that immunocytochemistry using Ki67 antibodies is a useful method of determination of proliferative activity of lymphoma cells, and have revealed high concordance between the results of Ki67 immunocytochemistry and immunohistochemistry performed on histological samples of lymphoma tissues.…”
Section: Application Of Cytology In Canine Lymphomassupporting
confidence: 48%
See 2 more Smart Citations
“…Ki67 ICC has also proved to be an excellent method of differentiation between non-neoplastic and neoplastic proliferation of lymphatic tissue (Bauer et al 2007, Fernandes et al 2015. Moreover, Fournel--Fleury et al (1997b) have confirmed that immunocytochemistry using Ki67 antibodies is a useful method of determination of proliferative activity of lymphoma cells, and have revealed high concordance between the results of Ki67 immunocytochemistry and immunohistochemistry performed on histological samples of lymphoma tissues.…”
Section: Application Of Cytology In Canine Lymphomassupporting
confidence: 48%
“…In the study of Munashinge et al (2015) the counting of Ki67 positive cells was performed in 500 cells, however, it is worth emphasizing that this analysis does not have to be so labor-consuming because counting as few as 100 cells is sufficient to obtain reliable results of Ki67 immunostaining (Bauer et al 2007). Counts can be performed in randomly chosen adjacent microscopic fields; however, unless positive cells are evenly distributed the analysis can be made in regions with the most intensive staining (Bauer et al 2007, Munashinge et al 2015.…”
Section: Application Of Cytology In Canine Lymphomasmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly (Vail et al, 1996;Vail et al, 1997;Fournel-Fleury et al, 1997b;Kiupel et al, 1998;Kiupel et al, 1999;Dank et al, 2002;Hipple et al, 2003;Whitten and Raskin, 2004;Vajdovich et al, 2004;Bauer et al, 2007). The most commonly (Vail et al, 1996;Vail et al, 1997;Fournel-Fleury et al, 1997b;Kiupel et al, 1998;Kiupel et al, 1999;Dank et al, 2002;Hipple et al, 2003;Whitten and Raskin, 2004;Vajdovich et al, 2004;Bauer et al, 2007).…”
Section: Lymphomamentioning
confidence: 99%
“…The most commonly used proliferation markers are mitotic index, percent positive for Ki-67 antigen, percent positive for proliferation cell nuclear antigen (PCNA), and argyrophilic nucleolar organizing regions (AgNOR) quantitation (Bauer et al, 2007;Dank et al, 2002;Fournel-Fleury et al, 1997b;Hipple et al, 2003;Kiupel et al, 1998;Kiupel et al, 1999;Vail et al, 1996;Vail et al, 1997;Vajdovich et al, 2004;Whitten and Raskin, 2004). The most commonly used proliferation markers are mitotic index, percent positive for Ki-67 antigen, percent positive for proliferation cell nuclear antigen (PCNA), and argyrophilic nucleolar organizing regions (AgNOR) quantitation (Bauer et al, 2007;Dank et al, 2002;Fournel-Fleury et al, 1997b;Hipple et al, 2003;Kiupel et al, 1998;Kiupel et al, 1999;Vail et al, 1996;Vail et al, 1997;Vajdovich et al, 2004;Whitten and Raskin, 2004).…”
Section: Lymphomamentioning
confidence: 99%